Quality of Recovery After Rotator Cuff Repair With Interscalene Liposomal Bupivacaine Versus Interscalene Nerve Catheter. Issue 11 (22nd November 2022) - Schoenherr, Jay W.; Gonzalez, Michael; Serrano, Ricardo; Park, Meredith; Lee, Zachary; Cobb, Kathryn; Howard, Christopher; Flynn, David; Li, Quefeng; Grant, Stuart; Bullard, Ty
Background: Interscalene nerve catheters have been proven to be effective in managing pain after rotator cuff repair (RCR) surgery. Liposomal bupivacaine is a newer approved therapy for use around the interscalene brachial plexus, but its analgesic efficacy has limited supporting data in various patient populations. Purpose/Hypothesis: The purpose of this study was to investigate the quality of recovery after arthroscopic RCR in patients who received either single-injection interscalene liposomal bupivacaine or an interscalene peripheral nerve catheter. It was hypothesized that interscalene peripheral nerve catheters would provide more reliable analgesia and improved patient satisfaction 48 hours after surgery. Study Design: Cohort study; Level of evidence, 2. Methods: Enrolled were 93 consecutive patients who underwent arthroscopic rotator cuff surgery at a single ambulatory surgery center between October 2020 and June 2021. Of these patients, 13 were lost to follow-up; thus, 80 patients were included in statistical analysis. One group of patients (n = 48) received a preoperative interscalene nerve block placed with 10 mL 0.5% bupivacaine and 10 mL 1.3% liposomal bupivacaine. The second group (n = 32) received a preoperative interscalene catheter with an initial bolus of 20 mL 0.25% bupivacaine and a 0.2% ropivacaine infusion by an elastomeric pump set at 10 mL/hr for 48 hours. The primary outcome was the difference between preoperative and 48-hour postoperative quality of recovery-15 (QoR-15) scores. Secondary outcomes included visual analog pain scores, opioid use, and patient satisfaction. Complications and adverse effects were also noted. The Kruskal-Wallis test was used to analyze means and standard deviations for continuous endpoints; Fisher exact test was used to analyze counts and proportions for categorical endpoints. Results: The liposomal bupivacaine group had a mean reduction of 3.9 in their postoperative QoR-15 scores, and the catheter group had a mean reduction of 25.1 in their postoperative QoR-15 scores, indicating a significantly worse functional recovery period compared with liposomal bupivacaine within the first 48 hours ( P < .001). Patients who received liposomal bupivacaine also had significantly lower pain scores on the second postoperative day, improved quality of sleep, and improved satisfaction with analgesia ( P < .05 for all). Conclusion: The use of interscalene liposomal bupivacaine demonstrated significantly improved quality of recovery when compared with interscalene nerve catheter after RCR.